Laser scribing of CIGS thin-film solar cell on flexible substrate - Hwang, David J.; Kuk, Seungkuk; Wang, Zhen; Fu, Shi; Zhang, Tao; Kim, Gayeon; Kim, Won Mok; Jeong, Jeung-hyun (SPRINGER HEIDELBERG, 2017)
Laser scribing technology has been actively developed for thin-film solar cell fabrication taking a number of advantages over mechanical scribing. Its non-contact processing nature enables reliable and precise scribing processes. In particular, it is almost unavoidable to use laser scribing method for fabricating high-quality flexible thin-film solar cells. Despite the fundamental merits that laser scribing can offer, still a number of challenges should be addressed in order to replace the mechanical counterpart for wider range of thin-film solar cells. In this study, we explore optimal laser scribing conditions for copper-indium-gallium-selenide (CIGS) thin-film solar cells, especially based on flexible polyimide (PI) substrate in close comparison with that based on soda-lime glass substrate. Picosecond-pulsed laser of repetition rate up to 100 kHz and wavelength of 532 nm (similar to 12 ps temporal pulse width) was mainly tested, and scribing speed in the range of 0.01-1 m/s was examined with a few different laser focal spot diameters (27, 34, and 62 mu m). Main focus of this study is in understanding distinct laser scribing mechanisms for flexible substrate configurations, thereby finding out intrinsic optimal processing parameters. One of the most critical requirements is to prevent possible damage or deformation of underlying thin-film layer(s) or PI substrate. Effect of microstructures of thin films (in particular, Mo and CIGS) on the scribing behavior was also examined. In order to further improve the performance of the scribing process and reduce the laser power budget as well, mild gas injection scheme was tested.